Eliciting trade-offs between water charges and service benefits in Scotland - Cameron A. Belton; Ciarán Lavin; Pete Lunn (The Economic and Social Research Institute (ESRI), 2020)
If it is the responsibility of a regulatory body to decide where to prioritise future investment, then it is important to understand the priorities of the citizenry it represents. This paper, in collaboration with the OECD and the Scottish water industry, presents the results of an online (n= 500) and face-to-face laboratory (n= 99) study that utilised experimental behavioural science to explore how Scottish citizens trade-off costs and potential improvements to their water service. Participants' priorities for investment were elicited using a novel 'slider task' methodology that forced them to explicitly consider the trade-offs required to allocate limited resources across multiple possible water service improvements. The provision of additional cost and timing information was systematically varied. Results suggest that citizens are increasingly accepting of price rises when provided this information. Results also suggest that citizens' priorities for specific improvements are not sensitive to the costs of different improvements but are sensitive to the lengths of time improvements take to be made. Findings from this study are designed to inform the regulatory process of the Scottish water industry and highlight the potential role of behavioural science in regulation more generally.
Keywords: 330; Wasserpreis; Experiment; Befragung; Schottland